Pregnanos e outros constituintes das raízes de Macrosiphonia petraea (A. St.-Hil.) Kuntze (Apocynaceae) - Luiz Roberto de Assis Junior; Fernanda Rodrigues Garcez; Walmir Silva Garcez; Zaira da Rosa Guterres (Química Nova, 2013)
Macrosiphonia petraea (A. St.-Hil.) Kuntze is a plant popularly known as "velame". Its root infusion is used in the folk medicine of Mato Grosso do Sul, Brazil, for the treatment of inflammatory diseases. Phytochemical investigation of the roots of this species led to the identification of 17 compounds belonging to four different classes: two pregnanes, 12β-hydroxypregna-4,6,16-triene-3,20-dione, neridienone A, and 12β-hydroxypregna-4,6-diene-3,20-dione, cybisterol, one hydroxylated fatty acid, 5-hydroxy-octadeca-6(E)-8(Z)dienoic acid, two lignoids, pinoresinol and 8a-hydroxypinoresinol, ten pentacyclic triterpenoids, and two steroids.